Determinants and Model for Estimating the Prevalence of Stunting Toddlers in Sleman Regency - Tri Siswati; Anif Muchlasin; Raden Yuli Kristyanto; Delima Citra Dewi Gunawan (Health Dynamics, 2024)
Background: The Sleman Regency Government is committed to solving the stunting problem by implementing an integrated stunting prevention program by encouraging the participation of penta-helix. Estimating stunting prevalence accomplishment targets is crucial for measuring progress, guiding strategies, and ensuring stunting reduction success. This study aims to provide information regarding the factors that contribute to the prevalence of stunted toddlers and develop a predictive model for that prevalence. Methods: The study investigated the prevalence of stunting, wasting, and underweight in Sleman Regency using publicly accessible reports, secondary data, and reputable websites. Data was gathered through audits of stunting cases and factors from district-level program managers, and analysed through desk reviews. This research was conducted in Sleman Regency from December 2023 to February 2024. Results: The investigation found that stunting is linked to family smoking, inadequate toddler nutrition, inactive JKN, chronic energy deficiency throughout pregnancy, and low-weight, preterm births. Through rules, policies, and multisectoral multistakeholder collaboration, the Sleman Regency Government aims to reduce stunting. The interventions include maternal and child health, nutritional counselling, drinking water and sanitation, early childhood education, and pre-conception family life preparation. A model to estimate long-term stunting prevalence is needed to track trends, evaluate interventions, and support evidence-based decision-making. Stunting is vital to public health and economic benefit. Based on audit data, child nutrition trends, and prediction models, Sleman Regency should reduce stunting by 0.02% per year for local data and 0.5% per year for national data. The determinants of stunting in Sleman Regency are very diverse, including problems related to nutrition and non-nutrition. Conclusion: Stunting prevention is focused on efforts to overcome habits, improve the nutritional status of pregnant women and optimize better pregnancy outcomes. Based on the analysis, the stunting reduction target was determined based on national and local surveys of 0.5% and 0.02% per year, respectively.Keywords: Under five children; estimation model; prevalence; stunting